Turismo como Mecanismo de Desenvolvimento Local e Empreendedorismo Sustentável: análise da demanda e do espaço rural do Alto Aiuruoca, Itamonte, MG - Couto, Renan Evangelista (2006)
Tourism has been shown as one of the most important worldwide industries. Its role as a sustainable development tool of the Alto Aiuruoca country area, in Itamonte district, Minas Gerais state, Brazil , was analysed considering aspects such as demand and residents point of view. The Residents are interested in undertaking and developing tourism with respect to the natural environment, tranquility and cultural preservation. This was verified through a social relationship, tourism seminaries, and questionnaires. Tourists are welcomed by the community of Alto Aiuruoca. Therefore, home lodging should be one of the options to assure sustainability of the area, although the community is interested in ensuring security and privacy. Rio de Janeiro and São Paulo are potential tourist providers. Questionnaires and interviews showed that persons with high social and cultural level are open to visit a place with Alto Aiuruoca characteristics, providing they find minimum comfort conditions. They are also interested in enjoying local gastronomy, culture, craftsmanship, etc, which are potential sources of revenue and work to residents.